2002
DOI: 10.1177/107110070202300807
|View full text |Cite
|
Sign up to set email alerts
|

The First Intermetatarsal Angle in Hallux Valgus: An Analysis of Measurement Reliability and the Error Involved

Abstract: In view of the importance placed on the first intermetatarsal angle in the assessment of surgical intervention in hallux valgus, we assessed the reliability with which one measures this angle. The study involved 10 observers of varying experience measuring the angle using a standard technique on 10 weightbearing AP X-rays of the foot on three separate occasions. The margin of error in measuring the angle was +/-3.60 degrees with a 95% confidence interval. Increasing and averaging the number of readings per obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 11 publications
2
40
1
3
Order By: Relevance
“…All of these coefficients can be considered very high, 42 so that the reproducibility of the measurements is acceptable with the methods used. 19,43 The The values from the descriptive analysis of the variables as absolute values are shown in Table 2. The values from the descriptive analysis of relative first metatarsal protrusion, and the comparison between the two groups, are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…All of these coefficients can be considered very high, 42 so that the reproducibility of the measurements is acceptable with the methods used. 19,43 The The values from the descriptive analysis of the variables as absolute values are shown in Table 2. The values from the descriptive analysis of relative first metatarsal protrusion, and the comparison between the two groups, are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The hallux valgus angle (HVA), 1-2 intermetatarsal angle (IMA), and distal metatarsal articular angle (DMAA) are all measured from the AP view ( Figure 1A). 13 The DMAA is the angle formed between the distal articular surface and longitudinal axis of the first metatarsal ( Figure 2). It is used to assess first MTP joint congruity, and <10 degrees is considered normal.…”
Section: Radiographic Examinationmentioning
confidence: 99%
“…Traditionally, HVA is measured by using a protractor and a marker pen with hardcopy radiographs. But it has been shown that this method is error‐prone and time‐consuming …”
mentioning
confidence: 99%